Hubungan Peran Keluarga dan Kepatuhan Pasien TB MDR di RSUD Dr. Soetomo Surabaya : [The Role of Family in Improving Multidrug-Resistant Tuberculosis Patient Compliance] - Safira Nur Ainiyah; Soedarsono Soedarsono; Pirlina Umiastuti (Jurnal Respirasi, 2019)
Background: Multi Drug Resistant Tuberculosis (MDR TB) is an infection disease caused by Mycobacterium tuberculosis and has been resistant to isoniazid and rifampicin. Based on medical record of MDR TB Clinic RSUD Dr. Soetomo Surabaya, there is an increase of drop out rate which indicates that MDR TB patient’s adherence is low althouh there are some policies to improve their adherence. Therefore family role is needed for increasing MDR TB patients’ adherence and decreaseing drop out rate.Objective: to know the relationship between family role and MDR TB patient’s adherence on treatment in RSUD Dr. Soetomo Surabaya. Method: This analytical study in cross sectional approach is held on October 2017-June 2018 in MDR TB Clinic of RSUD Dr. Soetomo Surabaya and patients’ house. There are 24 patients and their family which are enrolled and interviewed in this study. Inferential statistic which was Fisher Exact Test used to find out and analyze the relationship between family role and MDR TB patient’s adherence on treatment in RSUD Dr. Soetomo Surabaya. Result: There is no difference frequencies of high and low family role. The MDR TB patients have high adherence. There is significant (p = 0,018) and moderate (c = 0,452) relationship of family role and MDR TB patients’ adherence on treatment in RSUD Dr. Soetomo Surabaya.Conclusion: To improve MDR TB patients’ adherence, family must have a significant role and give support. Health provider also should give education about importance of family role in MDR TB patients’ treatment.